EFEKTIVITAS PENGELOLAAN SAMPAH RUMAH TANGGA DI KOTA MEDAN (STUDI KASUS DI KELURAHAN BINJAI KECAMATAN MEDAN DENAI) - Sihombing, Swanlayli Octrinda; Rusli, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Swanlayli Octrinda Sihombing. 1101112217. Efektivitas Pengelolaan Sampah Rumah Tangga di Kota Medan (Studi Kasus di Kelurahan Binjai Kecamatan Medan Denai). Advised by Dr. H. Zaili Rusli, M.Si.Population growth, changing consumption patterns and lifestyles of people have increased the amount of waste generation, types, and diversity characteristics of the waste. The increasing volume of waste requiring management. Waste management that does not use will be a negative impact on health will also be very disturb both environmental preservation of the residential environment, forest, rice fields, rivers and ocean.Types and methods of research used is descriptive research, which can be interpreted as a problem-solving process was investigated by depicting or describing the state of the subject and the object of research at the present time based on the facts that appear or how it is. While the methods used are qualitative research methods to describe the actual situation in detail and by looking at the actual problem and research objectives.There are 2 forms of participation that have been implemented in the Village of Binjai: Real Participation and Non-Real Participation. There are factors that affect the level of community participation in Binjai Village in waste management, which is gender, education level, length of stay, home ownership status, while age and income levels do not affect the level of community participation.Keywords: Effectivesness, Management, Waste.